(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Palatal mucormycosis in an infant is rare occurrence. Most commonly it is seen with hematological malignancy or solid tumors or immunodeficiency states like diabetes. Its association with urea cycle disorder is rarely reported. If left untreated mortality rate is very high. In our case KOH mount in view of unsual palatal growth was done which later confirmed with MRI brain to rule out any CNS involvement. All supportive measures were provided. But because of extreme hemodynamic instability with coexisting enterococcus sepsis the infant succumbed due to severe disseminated intravascular coagulation & septic shock. We should consider the possiblity of fungal infections in debilitating patients who are not improving on broad spectrum antibiotics & to consider the prophylactic use of iv amphotericin B whenever there is high index of clinician suspicion even if initial reports were normal.